Measuring the Psychological Distance between an Organization and Its Members—The Construction and Validation of a New Scale - Chen, Hong; Li, Shanshan (Frontiers in Psychology, 2018)
There exists a lack of specific research methods to estimate the relationship between an organization and its employees, which has long challenged research in the field of organizational management. Therefore, this article introduces psychological distance concept into the research of organizational behavior, which can define the concept of psychological distance between employees and an organization and describe a level of perceived correspondence or interaction between subjects and objects. We developed an employee-organization psychological distance (EOPD) scale through both qualitative and quantitative analysis methods. As indicated by the research results based on grounded theory (10 employee in-depth interview records and 277 opening questionnaires) and formal investigation (544 questionnaires), this scale consists of six dimensions: experiential distance, behavioral distance, emotional distance, cognitive distance, spatial-temporal distance, and objective social distance based on 44 items. Finally, we determined that the EOPD scale exhibited acceptable reliability and validity using confirmatory factor analysis. This research may establish a foundation for future research on the measurement of psychological relationships between employees and organizations.